Use of an innovative system and nanotechnology-based strategy for therapeutic applications of Gla-rich protein (GRP) - Viegas, Carla (2020)
Introduction: Gla-rich protein (GRP) is a vitamin K-dependent protein (VKDP) acting as a calcification inhibitor and anti-inflammatory agent in cardiovascular and articular systems, and THP1 monocyte/macrophage cells [1,2]. Calcification and inflammation processes are known to be involved in the etiology of several calcification-related chronic inflammatory diseases such as atherosclerosis, CKD and osteoarthritis, in a complex bi-directional interplay that drives disease progression. Here, we developed an innovative system to produce human c-carboxylated GRP (cGRP), and a nanotechnology strategy based on GRP loading into extracellular vesicles (EVs) as a gold standard delivery system for GRP in therapeutic applications. Materials and methods: Human GRP protein was co-expressed with c-carboxylase enzyme (GGCX), vitamin K oxidoreductase (GGCX) and furin, in the insect cell baculovirus system in the presence of vitamin K. GRP released in the cell culture media was characterized by mass spectrometry based techniques and Western blot analysis. EVs released by the insect cells overexpressing GRP were isolated by ultracentrifugation, and characterized for GRP content through TEM-immunogold staining, Western blot, ELISA, qPCR. Functional assays using isolated EVs containing GRP were performed in primary vascular smooth muscle cells (VSMCs) and THP1 monocyte/macrophage cells, for anti-mineralizing and anti-inflammatory screening.Results: GRP released in the cell culture media when co-expressed with GGCX, VKOR and furin in the presence of vitamin K, is processed at the pro-peptide and contain Gla residues. EVs released by the insect cells in this system were shown to be loaded with GRP protein and mRNA, and capable of reducing ECM calcium deposition of calcifying VSMCs and the production of TNFa in THP1 monocyte/macrophage cells stimulated with LPS. Discussion and conclusions: While the successful production of human cGRP constitutes a major achievement, this innovative methodology will open new opportunities for the production of other biological active VKDPs. Furthermore, EVs loaded with GRP were shown to have anti-mineralizing and anti-inflammatory properties, with promising therapeutic potentialities for calcification-related chronic inflammatory diseases.